Toward a Liberalism - Flathman, Richard E. (Book collections on Project MUSE., 1989)
In Toward a Liberalism, Richard Flathman shows why and how political theory can contribute to the quality of moral and political practice without violating, as empiricist- and idealist-based theories tend to do, liberal commitments to individuality and plurality. Exploring the tense but inevitable relationship between liberalism and authority, he advances a theory of democratic citizenship tempered by appreciation of the ways in which citizenship is implicated with and augments authority. Flathman examines the relationship of individual rights to freedom on one hand and to authority and power on the other, rejecting the quest for a single homogenous and authoritative liberal theory.